Specular and diffusive reflectance of stainless steel mirrors sputtered with Ar⁺ ions - Konovalov, V.G.; Bondarenko, V.N.; Ryzhkov, I.V.; Shapoval, A.N.; Shtan’, A.F.; Skoryk, O.O.; Solodovchenko, S.I.; Voitsenya, V.S. (Вопросы атомной науки и техники, 2012)
It was shown that a light source with edge sharpness can be used for very sensitive measurements of the ratio of specular and diffusive components of reflectance of the mirror subjected to sputtering. Измерение изображения резко очерченного источника света, отраженного от зеркала (IQ-метод), является очень чувствительным методом регистрации соотношения зеркального и диффузного компонентов коэффициента отражения при распылении испытуемых образцов. Вимірювання зображення різко окресленого джерела світла, відбитого від дзеркала (IQ-метод), є дуже чутливим методом реєстрації співвідношення дзеркального та дифузного компонентів коефіцієнта відбиття при розпиленні випробовуваних зразків.